The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/zsc.12271
|View full text |Cite
|
Sign up to set email alerts
|

Integrative taxonomy of the neotropical genus Omalonyx (Elasmognatha: Succineidae)

Abstract: The genus Omalonyx d'Orbigny, 1837, includes neotropical semi‐aquatic succineid slugs and comprises six recognized species to date. Field surveys across continental South America recovered five of the six recognized species. According to the morphological characters traditionally included in Omalonyx descriptions, the specimens were tentatively identified as O. matheroni, O. pattersonae, O. convexus, O. geayi and O. unguis. Employing sequences of mitochondrial cytochrome oxidase I (COI) alone or combined with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…The members of the evandroi complex may be in an incipient sympatric speciation process, in which only a few loci involved in the differentiation of genitalia – the morphological structure that distinguishes between them – might be involved. Morphologically‐distinct taxa comprising a single molecular group have been previously observed in various organisms, including land snails (Stankowski & Johnson, 2014; Vidigal et al ., 2018), reef sponges (DeBiasse & Hellberg, 2015), octocorals (Ament‐Velásquez et al ., 2016) and lizards (Jin et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The members of the evandroi complex may be in an incipient sympatric speciation process, in which only a few loci involved in the differentiation of genitalia – the morphological structure that distinguishes between them – might be involved. Morphologically‐distinct taxa comprising a single molecular group have been previously observed in various organisms, including land snails (Stankowski & Johnson, 2014; Vidigal et al ., 2018), reef sponges (DeBiasse & Hellberg, 2015), octocorals (Ament‐Velásquez et al ., 2016) and lizards (Jin et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, due to misconceptions and contradictions in Omalonyx systematics, those previous records should be interpreted with caution as they may include what today is recognized as O. convexus (Arruda and Thomé 2008a). Despite this, the records reported herein constitute the first anatomically and molecularly confirmed occurrences of O. unguis in Misiones and increase Vidigal et al (2018). Circles indicate the new localities where the specimens of O. unguis were found in Misiones Province, Argentina.…”
Section: Discussionmentioning
confidence: 59%
“…Our BLASTN searches of the COI sequences revealed that samples of O. unguis from Itá, Zaimán, and Garupá streams were identical (100% query coverage, 100% maximum identity) to Foz do Iguaçu, Brazil samples, whereas our sample from Mártires stream was identical (100% query coverage, 100% maximum identity) to sequences from a tributary stream of the Paraguay River, as well as with High Paraná River samples from locations situated before its confluence with the Paraguay River. On the other hand, DNA sequences from the remaining samples differed from the previously characterized by Vidigal et al (2018), thus representing new haplotypes. Further research is required to gain insights into the genetic background of the O. unguis populations in Misiones Province, as the molecular data presented here represent the first DNA sequences for the species in Argentina.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations